Building information modelling (BIM) adoption in contractor organisations / Wan Nur Syazwani Wan Mohammad, Mohd Rofdzi Abdullah and Sallehan Ismail - Wan Mohammad, Wan Nur Syazwani; Abdullah, Mohd Rofdzi; Ismail, Sallehan (2018)
The construction industryhas been facing various problems such as low investment rate, rising cost, additional risks, and wastein labour productivity whichled to a decline in the quality of life of the construction stakeholders. To date, Building Information Modelling (BIM) has been used to improve visualization and productivity;to better coordinate construction drawings and communication;to provide faster delivery; and to lower costs. However, the adoption of BIM among Malaysian contractors organisations has been low and stagnant.Hence, this research aims to gainan overview of BIM adoption among contractors organisations as well as to investigate the reasons for the low adoption among contractors organisations. A qualitative approach in the form of semi-structured interview was used in this study to explore BIM adoption among contractors organisations. The findings were subsequently analysed using content analysis. The findings indicated that contractors organisations in Malaysia have no framework or model. Hence, developing the BIM adoption framework or model is urgently needed to encourage the development of BIM in Malaysia.